Temperature and polarization dependent Raman spectra of liquid H2O and D2O. (10th September 2018) - Pattenaude, Shannon R.; Streacker, Louis M.; Ben‐Amotz, Dor
Abstract: Polarized Raman spectra of liquid H2 O and D2 O have been measured over the entire 100 to 4, 000 cm −1 vibrational frequency range and 280 to 360 K temperature range. The measured spectra are corrected for wavelength‐dependent detector quantum efficiency and are provided in numerical form to facilitate comparisons with theoretical predictions. Self‐modeling curve resolution is used to decompose the measured spectra into a linear combination of two spectral components whose relative intensities change with temperature but whose shapes are approximately temperature independent. The component whose intensity increases with decreasing temperature contains prominent features in both the high‐frequency OH stretch band region and low‐frequency OH⋯O hydrogen bond stretch band region that resemble those observed in single crystal ice Ih and clathrate hydrates. Abstract : Polarized Raman spectra of liquid H2 O and D2 O have been measured over the entire 100 to 4, 000 cm −1 vibrational frequency range and 280 to 360 K temperature range. Self‐modeling curve resolution is used to decompose the measured spectra into a linear combination of two spectral components whose relative intensities change with temperature but whose shapes are approximately temperature independent.